Synthesis of reactive waterborne polyurethane modified with quaternary ammonium chain extender and its color fixation properties. Issue 7 (3rd July 2017) - Fan, Zenglu; Li, Qing; Cai, Xinbin; Li, Zhibin
Abstract: N-Methyl diethanolamine was adopted to react with isophorone diisocyanate to provide a dihydroxyl complex. The obtained complex was further modified by benzyl chloride through alkylation reaction to offer a cationic quaternary ammonium chain extender. Polyether glycol was selected as the soft segment to prepare the waterborne polyurethane (WPU) prepolymer. Then, as-prepared cationic chain extender was blocked into the achieved WPU prepolymer, and the residual NCO groups were tentatively terminated by NaHSO3 at a low temperature to obtain WPU emulsion. The structure of WPU was confirmed by Fourier Transform Infrared spectrometry, Gel permeation chromatography, Thermogravimetric analysis, and scanning electron microscopy. The color fastness of dyed cotton fabrics was obviously promoted after treating by WPU latex, and the wet rubbing fastness of cotton fabrics obviously improved 1.5 grade.